2020
DOI: 10.3390/molecules25184154
|View full text |Cite
|
Sign up to set email alerts
|

Dibromopinocembrin and Dibromopinostrobin Are Potential Anti-Dengue Leads with Mild Animal Toxicity

Abstract: Dengue infection is one of the most deleterious public health concerns for two-billion world population being at risk. Plasma leakage, hemorrhage, and shock in severe cases were caused by immunological derangement from secondary heterotypic infection. Flavanone, commonly found in medicinal plants, previously showed potential as anti-dengue inhibitors for its direct antiviral effects and suppressing the pro-inflammatory cytokine from dengue immunopathogenesis. Here, we chemically modified flavanones, pinocembri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 49 publications
3
25
0
Order By: Relevance
“…Flavanones (e.g., hesperetin), flavanol (e.g., quercetin), , and flavone (e.g., baicalein) exhibit antiviral activities. Interestingly, a recent study has reported SARS-CoV-2 inhibition by baicalein (IC 50 0.94 ± 0.20 μM) and its cocrystallized structure with 3CL pro 10 . Apart from the 3CL pro in SARS-CoV-2, halogenated modification of the baicalein scaffold by halogen atoms bonding to carbon (C–X) of an aromatic ring could improve bioactivity. , Brominated baicalein (8-bromobaicalein) has shown the greatest inhibitory effect against the breast cancer cell line MCF-7 (IC 50 10 ± 3 μM) by blocking the human protein kinase CK2 . Typically, the halogen atom on the aryl halide shows an anisotropic charge distribution that can form a halogen interaction (XB).…”
Section: Introductionmentioning
confidence: 99%
“…Flavanones (e.g., hesperetin), flavanol (e.g., quercetin), , and flavone (e.g., baicalein) exhibit antiviral activities. Interestingly, a recent study has reported SARS-CoV-2 inhibition by baicalein (IC 50 0.94 ± 0.20 μM) and its cocrystallized structure with 3CL pro 10 . Apart from the 3CL pro in SARS-CoV-2, halogenated modification of the baicalein scaffold by halogen atoms bonding to carbon (C–X) of an aromatic ring could improve bioactivity. , Brominated baicalein (8-bromobaicalein) has shown the greatest inhibitory effect against the breast cancer cell line MCF-7 (IC 50 10 ± 3 μM) by blocking the human protein kinase CK2 . Typically, the halogen atom on the aryl halide shows an anisotropic charge distribution that can form a halogen interaction (XB).…”
Section: Introductionmentioning
confidence: 99%
“…Binding free energy computed by MMGBSA or MMPBSA algorithms have been widely employed to predict the binding affinity of protein-ligand [ 38 , 39 , 40 , 41 ] and protein-protein complexes [ 16 , 42 , 43 , 44 ] and is in good agreement with experimental findings. In this work, binding free energy of Ank GAG 1D4 and Ank GAG 1D4-Y56A for HIV-1 CA was computed to understand the effect of single point mutation performed on residue Y56 of Ank GAG 1D4.…”
Section: Discussionmentioning
confidence: 75%
“… 43 A halogen-substituted compound has also been considered in drug discovery and design. 44 46 The pharmacological properties of these compounds were also predicted to verify whether these screened pyrazolone derivatives can be used as a good candidate for JAKs inhibitors. All the screened compounds obey Lipinski’s rule 47 ( Table S1 ), suggesting that they could be candidates for novel JAK2/3 inhibitors.…”
Section: Resultsmentioning
confidence: 99%